2006
DOI: 10.1097/01.mph.0000195296.48319.38
|View full text |Cite
|
Sign up to set email alerts
|

Argatroban Anticoagulation in Pediatric Patients

Abstract: Argatroban, a direct thrombin inhibitor, is approved in the United States in adults as an anticoagulant for prophylaxis or treatment of thrombosis in heparin-induced thrombocytopenia (HIT) and in adults with or at risk for HIT undergoing percutaneous coronary intervention. The authors conducted a literature analysis to characterize the uses, dosing patterns, and safety of argatroban anticoagulation in pediatric patients. A comprehensive literature search identified nine articles describing 34 patients aged 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 27 publications
(34 reference statements)
0
40
0
1
Order By: Relevance
“…This included 2 case reports about the same patient [16, 17], a case report [18] and follow-up letter to the editor [19] on the same patient, a case report on a pediatric patient [20] who was also in a case series of argatroban-treated pediatric patients [21], and a case series of 6 patients with HIT after heparin exposure solely for RRT [11], of which each patient was also in a report on 47 patients with HIT requiring RRT [22]. For these article pairs, only the earlier [16, 18] or broader-scoped [21, 22] publication was included in the literature set. Additional search strategies, primarily review of bibliographies, found another 7 relevant publications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included 2 case reports about the same patient [16, 17], a case report [18] and follow-up letter to the editor [19] on the same patient, a case report on a pediatric patient [20] who was also in a case series of argatroban-treated pediatric patients [21], and a case series of 6 patients with HIT after heparin exposure solely for RRT [11], of which each patient was also in a report on 47 patients with HIT requiring RRT [22]. For these article pairs, only the earlier [16, 18] or broader-scoped [21, 22] publication was included in the literature set. Additional search strategies, primarily review of bibliographies, found another 7 relevant publications.…”
Section: Resultsmentioning
confidence: 99%
“…A literature review of argatroban use in pediatrics [21] described 5 patients between 2.5 months and 16 years old, each with current or previous HIT, who underwent RRT. Anticoagulation was provided with argatroban 0.1–2 µg/kg/min (with an initial 65 µg/kg bolus in 1 patient), adjusted to achieve target ACTs of 160–180 (n = 3) or 180–200 s (n = 1) or target aPTTs >50 s (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Although information in the literature is extremely scarce, argatroban is used to replace heparin therapy if HIT is suspected in children who are dependent on sufficient anticoagulation such as during extracorporeal circulation or in the presence of cardiac assist devices [25,26]. Due to the effect of argatroban on PT/INR, the transition from argatroban to oral vitamin K antagonists is difficult to manage.…”
Section: New Anticoagulantsmentioning
confidence: 99%
“…In general argatroban can be discontinued when the INR is > 4 and repeated INR 4 to 6 hours after discontinuation of argatroban remains in the target INR range. Argatroban is the only thrombin inhibitor approved for children [25].…”
Section: New Anticoagulantsmentioning
confidence: 99%
“…Anekdotische Berichte zeigen, dass bei Kindern mit HIT nach Verschwinden der HIT-Antikörper die Antikoagulation zur HLM erfolgreich mit unfraktioniertem Heparin, Aprotinin und Tirofiban durchgeführt werden konnte [76]. Zur Verwendung von alternativen Antikoagulanzien in heterogenen Therapieregimen gibt es Fallberichte [77,78,79,80,81].…”
Section: Herzlungenmaschine Beim Kindernunclassified